Intramuscular injection of dexamethasone for the control of pain, swelling, and trismus after third molar surgery: a systematic review and meta-analysis. Issue 5 (May 2019) - Fernandes, I.A.; de Souza, G.M.; Pinheiro, M.L.P.; Falci, S.G.M.
Abstract: This systematic review aimed to answer the following PICO question: Does the intramuscular injection of dexamethasone result in less pain, swelling, and trismus after mandibular third molar removal when compared to other routes of administration or a control group (saline solution injection or no treatment)? An electronic search was conducted in Virtual Health Library, PubMed, and Web of Science, through March 2018. Eligibility criteria included clinical trials. The search strategy resulted in 331 studies. Following the selection process, 15 articles were included in the systematic review; eight of these were included in the meta-analysis. Most of the studies had an unclear risk of bias (Cochrane Handbook assessment). Pain (mean difference (MD) −1.58, 95% confidence interval (CI) −1.99 to −1.16) and oedema (MD −1.76, 95% CI −2.38 to −1.14) were lower in the intramuscular dexamethasone group when compared to the control group. When compared to the submucosal route, the intramuscular route was more effective only for pain on the third postoperative day (MD −0.79, 95% CI −1.38 to −0.20). The results suggest that the intramuscular injection of dexamethasone may be an alternative route of administration, since it is effective at reducing pain and oedema when compared to non-steroidal treatment and has similar results to the submucosal route.